2018
DOI: 10.1002/cctc.201800204
|View full text |Cite
|
Sign up to set email alerts
|

Ni‐Ce/Zeolites for CO2 Hydrogenation to CH4: Effect of the Metal Incorporation Order

Abstract: a] InÞsG raÅa, [b] JosØ M. Lopes, [a] andC arlosH enriques* [a] Introduction CO 2 methanation, as af orm of alleviating CO 2 emissions, has been the focus of much attention in the last few years, with thermal, photocatalytic,e lectrochemical, or even plasma assisted processes being used. [1][2][3][4][5][6] Ni and Ru-based materials have been commonly used for this reaction, on different supports, such as Al 2 O 3 , [7][8][9][10][11][12][13][14][15] SiO 2 , [16][17][18][19][20] Ce and Zr oxides, [21][22][2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 58 publications
4
23
0
1
Order By: Relevance
“…In addition, Bacariza et al . optimized the impregnation strategy for the synthesis of NiCe/USY zeolites (Figure ).…”
Section: Co2 Methanation Over Zeolite‐based Catalysts Under Thermal Csupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, Bacariza et al . optimized the impregnation strategy for the synthesis of NiCe/USY zeolites (Figure ).…”
Section: Co2 Methanation Over Zeolite‐based Catalysts Under Thermal Csupporting
confidence: 89%
“…Authors found out that co‐impregnation favours Ni and Ce species interaction, enhancing the metallic dispersion and the CO 2 adsorption/activation. Indeed, the optimized sample reported by the authors in this work presented higher performances than a commercial Ni‐based alumina catalyst…”
Section: Co2 Methanation Over Zeolite‐based Catalysts Under Thermal Csupporting
confidence: 89%
See 3 more Smart Citations